Identification and characterization of a major QTL underlying soybean isoflavone malonylglycitin content - Watanabe, Satoshi (Breed Sci, 2019)
Isoflavones in soybean seeds are responsible for plant–microbe interactions and defend against pathogens, and are also beneficial to human health. We used two biparental populations and mini core collection of soybean germplasm to identify and validate QTLs underlying the content of isoflavone components. We identified a major QTL, qMGly_11, which regulates the content of malonylglycitin, on chromosome Gm11, in populations bred from parents with high, low, and null glycitein contents. qMGly_11 explained 44.5% of phenotypic variance in a population derived from a cross between ‘Aokimame’ (high) and ‘Fukuyutaka’ (low) and 79.9% of that in a population between ‘Kumaji-1’ (null) and ‘Fukuyutaka’ (low). The effect was observed only in the hypocotyl. We further confirmed the effect of qMGly_11 in a mini-core collection, where it explained 57.1% of the genetic diversity of glycitin production and 56.5% of malonylglycitin production. qMGly_11 increased the contents of glycitin and malonylglycitin at the expense of daidzin and malonyldaidzin in all analyzed populations. We discuss the gene responsible for this QTL and the availability of the null allele for metabolic engineering of soybean seed isoflavones.